Removal of selected antibiotics and antiretroviral drugs during post‐treatment of municipal wastewater with UV, UV/chlorine and UV/hydrogen peroxide. (6th July 2020) - Ngumba, Elijah; Gachanja, Anthony; Tuhkanen, Tuula
Abstract: Active pharmaceutical ingredients (APIs) are only partially removed by convectional wastewater treatment plants. This study aimed at assessing the post‐treatment degradation of selected antibiotics and antiretroviral drugs by direct UV photolysis and advanced oxidation processes (UV/H2 O2 and UV/Cl2 ) using low‐pressure mercury lamp. The rate of degradation largely followed pseudo first‐order reaction kinetics. Amongst the six studied APIs, sulfamethoxazole, ciprofloxacin and zidovudine were readily degraded by more than 90% using direct UV photolysis. Addition of Cl2 and H2 O2 to the UV process led to an increase in the rate of degradation for all the compounds. The effectiveness UV/Cl2 process was affected to a greater extent by the background effluent organic matter. This implies that higher electrical energy and oxidant would be required in the UV/Cl2 process relative to UV/H2 O2 process. Generally, electrical energy required to remove 90% of the target compounds increased in the order UV/H2 O2 < UV/Cl2  < UV processes.